Influence of discrete fracture network on the performance of enhanced geothermal system considering thermal-hydraulic-mechanical multi-physical field coupling. - Haiyang Jiang; He Huang; Liangliang Guo; Yanling Cao; Yanchun Hu; Su Cui; Bo Wu; Fengxin Kang; Ling Zhang; Meng Shi; Xueyu Zhou (PLoS ONE)
The long-term circulation of cold water within the deep heat reservoir in enhanced geothermal system (EGS) involves dynamic evolution of thermal-hydraulic-mechanical (THM) fields. The characteristics of discrete fracture network (DFN) in the reservoir also affect the thermal performance of EGS. In this paper, the influence of the DFN on the performance of EGS considering THM multi-physical field couple was numerically investigated. The effect of water property change and cold tension stress with temperature was considered. The influence of DFN characteristics (fracture density, fracture aperture, angle between fracture and well connection line and fracture pattern) was discussed. Results indicate that the effect of considering water property change on the Darcy velocity is larger than considering the stress field. Considering water property change and stress field both lead to a larger Darcy velocity of the fracture water and make the temperature field drop faster. With the increase of fracture density, the production Darcy's velocity increases gradually and the difference in thermal recovery efficiency is significant. Fracture aperture has a greater influence on the temperature field of the whole DFN reservoir than fracture density. The larger the fracture aperture, it will take away the heat energy from the heat reservoir faster. The smaller the angle between fracture and well connection line, the smaller the flow resistance of the working fluid, and the larger the equivalent permeability of the reservoir DFN system. The differences in the seepage field are small for the same range of statistical characteristics and parameter values for the DFN patterns. The DFN system with uniform fracture distribution should be selected for a better EGS reservoir, and the angle between the direction of the main fracture group and the direction of the well connection line should be at a certain acute angle.